THU0455 Disruptive Pathology Rather than Degenerative OR Discrete Tear are Associated with Increasing Bone Marrow Lesion Volume and a Proxy for Total Knee Arthroplasty: Longitudinal Analysis from the Osteoarthritis Initiative. (9th June 2015) - Eathakkattu Antony, B.S.; Driban, J.; Lyn Price, L.; Lo, G.; Ward, R.; Eaton, C.; Lynch, J.; Nevitt, M.; Ding, C.; McAlindon, T.
Abstract : Background: It is unknown if different types of meniscal pathology are associated with knee osteoarthritis (OA). Objectives: To explore the association of different types of knee meniscal pathology with bone marrow lesion (BML) volume, change in BML volume over 2 years, and a proxy for total knee arthroplasty (TKA). Methods: We selected a convenience sample of the Osteoarthritis Initiative (OAI) who had symptomatic knee OA and complete data for the OAI Bone Ancillary Project. A musculoskeletal radiologist reviewed the 24-month OAI magnetic resonance (MR) images for meniscal pathology by location within the medial and lateral menisci using a modified International Society of Arthroscopy, Knee Surgery, and Orthopaedic Sports Medicine (ISAKOS) meniscal tear classification system. For analyses, we reclassified the 10 original ISAKOS categories into 5 categories: normal, degenerative signal, morphological deformity, any tear (i.e., horizontal, horizontal flap, longitudinal-vertical, radial, vertical-flap, complex tear), and maceration. Total number of regions affected by meniscal pathology (0-6) was calculated by counting the number of regions that had pathologic findings. BML volume assessment was performed using a semi-automated segmentation method at 24 and 48 month visits. We categorized the 24-month BML volume into 3 categories: 1) no meaningful BML volume (<1cm 3 ), 2) ≥1 cm 3 and below median (2.15cm 3 ) and 3) above median of BML volume. Change in BML volume was categorized to 4 groups: 1) no meaningful BML volume (<1cm 3 ) at both time points, 2) lowest quartile of meaningful BML volume change (BML volume change ≤-0.75 cm 3 ), 3) middle 2 quartile of the BML volume change (BML volume change >-0.75 cm 3 &≤1.00 cm 3 ), 4) highest quartile of the BML volume change (BML volume change >1.00 cm 3 ). We categorized the proxy for TKA into appropriate and non-appropriate based on the algorithm developed by Escobar et al and adapted to OAI 1 . Results: 400 participants were included in the analysis with mean age of 63 (9.2) years, 53% male, body mass index 29.6 (4.6) kg/m 2, 71% Kellgren-Lawrence grade ≥2, and with 86% having any meniscal pathology. There was a significant association between any meniscal pathology with BML volume (OR:3.87) and change in BML volume (OR:2.32) but not with proxy for TKA. Having more number of regions of the menisci affected with pathology was associated with greater BML volume, change in BML volume, and proxy for TKA than those with a normal meniscus. Morphological deformity and maceration were associated with BML volume, change in BML volume, and proxy for TKA. Removing surgery or injury cases did not change our results. Conclusions: Among the five categories of meniscal pathologies, disruptive pathology rather than degenerative or discrete tear was associated with structural changes and a later clinical state that is proxy for TKA. This suggests that pathologies that impair normal load distribution properties of meniscus can cause damage to the knee joint. References: Riddle DL, et al. Arthritis Rheumatol. Aug 2014;66(8):2134-2143. Disclosure of Interest: None declared